ANALYSIS OF “SURE” IN “THE BLACKWATER LIGHTSHIP” FROM THE PERSPECTIVE OF HALLIDAY’S SYSTEMIC FUNCTIONAL LINGUISTICS - Thandar Zan (Language Circle: Journal of Language and Literature, 2026)
This paper explores the role of the word “Sure” in the characters’ dialogues in Colm Tóibín’s Irish Novel The Blackwater Lightship. The dialogue in the novel serves as a trace of the language within the literary context. This study applies the framework of Halliday’s SFL to analyze the “Sure” into two levels in the methods of discourse and comparative analysis: (1) On the micro level, “Sure” is analyzed as a discourse marker and an adjunct mood within the dialogue. The study compares its usage in Irish English with other English varieties, particularly American English, using concordances from the Corpus of Contemporary American English to highlight differences. (2) On the macro level, the research is framed within Halliday’s “Beyond the Clause,” exploring the multifunctional role of “Sure” in Irish English. The findings show that “Sure” can simultaneously serve both functions as a marker of agreement or emphasis and the adjunct modal for its headed clause. “Sure” was intentionally employed by authors in dialogue to enhance interpersonal meaning, supporting character interactions, and influencing the narrative’s overall coherence. This study contributes to the distinct linguistic feature of Irish English and its significance in interaction, which represents the entire society.